A New Editor-in-Chief Takes Over. Issue 2 (30th December 2015) - Pringot, Jacques
A reformatted journal demands a new Editor-in-Chief. Over the last year, the paper-printed Journal of the Belgian Society of Radiology has gone through a radical and successful transformation into a fully electronic open medium on an advanced IT platform. The time has thus become right for me to step down as Editor-in-Chief